An Analysis of English Mid-Term Test Items at the 7th Grade Students of SMPN 7 Bukittinggi - Raihana, Salsa Billa; Dewi, Merry Prima; Syahrul, Syahrul; Irwandi, Irwandi (Pusdikra-Publishing.com, 2024)
This study was motivated by several problems, such as the mismatch between the test questions and the material learned, unclear question instructions, and the lack of statistical analysis by English teachers. The main objective of this study was to identify the quality of English midterm test items for grade 7th students at SMPN 7 Bukittinggi, focusing on Validity, Reliability, difficulty level, Discrimination Power, and Distractor Effectiveness. The research method used was Quantitative Descriptive, with data collection through student answer sheets and analysis using various statistical formulas, including Point Biserial Correlation for validity, Spearman-Brown for reliability, and Narsya's formula for difficulty level and differentiating power, as well as Djumingin's formula for effectiveness. The results showed that most of the items were valid, and reliable, had a moderate difficulty level, and had good discriminating power, with only a few items showing minor problems. Overall, the English midterm exam items were considered good quality.